AI Art and Cultural Identity: From Photographic Image to Algorithmic Image as Cultural Sign(A study based on the Saudi cultural context) (Al-Academy, 2026)
The artworks produced in this study Works both as creative outcomes and as methodological tools. By transforming photographic images into AI-generated visual images, the artworks became a research site for examining shifts in cultural representation. The study aimed to investigate how meaning changes when an image moves from photographic representation to algorithmic representation through a visual experiment based on artificial intelligence. In photographic images, meaning is generally associated with documentation and real-world context, whereas in algorithmic images it is reconstructed through processes of generation and computational interpretation. This transformation provides a framework for examining how cultural identity is represented and reconfigured. To achieve these objectives, the study adopted both a technology-based research approach and a practice-based research methodology, as these were considered most suitable for exploring the research questions. The findings revealed that the transition from photographic to algorithmic imagery constitutes a process of reconstructing cultural meaning, in which artificial intelligence becomes an active participant in the production of meaning and the representation of identity. The study recommends that visual arts researchers adopt technology-based and practice-based methodologies to better understand artistic and cultural transformations in the age of artificial intelligence.